2021
DOI: 10.1021/acs.bioconjchem.0c00694
|View full text |Cite
|
Sign up to set email alerts
|

MOFs-Derived Fe–N Codoped Carbon Nanoparticles as O2-Evolving Reactor and ROS Generator for CDT/PDT/PTT Synergistic Treatment of Tumors

Abstract: Metal–organic frameworks (MOFs) derivatives had been widely explored in electronic and environmental fields, but rarely evaluated in the biomedical applications. Herein, Fe–N codoped carbon (FeNC) nanoparticles were synthesized and characterized via facile pyrolysis of precursor ZIF-8 (Fe/Zn) nanoparticles, and their potential applications in tumor therapy were assessed in this investigation both in vitro and in vivo. After PAA (sodium polyacrylate) modification, the FeNC@PAA nanoparticles were able to initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 51 publications
0
47
0
Order By: Relevance
“…Recently, the CDT/PDT combination therapy has been widely used in tumor therapy due to its excellent synergistic therapeutic effect. [23,24] Generally speaking, PDT consists of three basic components: a photosensitizer, light, and oxygen. [25,26] Photosensitive (PS) agents accept laser energy and convert O 2 into a highly reactive product ( 1 O 2 ) under light irradiation, which rapidly causes cell death via apoptosis or necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the CDT/PDT combination therapy has been widely used in tumor therapy due to its excellent synergistic therapeutic effect. [23,24] Generally speaking, PDT consists of three basic components: a photosensitizer, light, and oxygen. [25,26] Photosensitive (PS) agents accept laser energy and convert O 2 into a highly reactive product ( 1 O 2 ) under light irradiation, which rapidly causes cell death via apoptosis or necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…A 21-day mice study demonstrated that the synthesized nanoparticles can control the tumor growth, and it was observed that the tumor weight was reduced approximately 53 times smaller than the PBS (-) group. The treatment approaches also ensure the low biotoxicity of nanoparticles in in vivo, and there were no noticeable weight changes and histopathological damages in all the studied groups [61]. Zheng et al (2016) synthesized protoporphyrin-loaded and Arg-Gly-Asp (RGD) targeting motif coated carbon nitride-based multifunctional nanocomposite for enhanced PDT.…”
Section: Carbon-based Nanoparticlesmentioning
confidence: 98%
“…MOF derivatives based on MOF as sacrificial templates are for high loading anticancer drugs (Tang et al, 2017). Carbon nanostructure-containing PMCS from MOFs have excellent properties of sonosensitizer for SDT (Pan et al, 2018), photothermal conversion for PTT (Weng et al, 2020) and for CDT/PDT/PTT (Sui et al, 2021), and PAI-guided photothermal/ photodynamic combination therapy (Yang et al, 2018a). Besides, ultrasmall porphyrinic MOF nanodots (MOF QDs) prepared from NMOFs could generate twofold effective ROS and thus benefit enhanced PDT.…”
Section: Metal-organic Framework Derivativesmentioning
confidence: 99%